Hubungan Self-Efficacy dengan Self-Care Management pada Lansia Penderita Hipertensi di Wilayah Kerja Puskesmas Rangkasbitung - Farah Luqyana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Elderly individuals undergo various physical, psychological, and social changes that increase their risk of developing diseases, including hypertension. As hypertension is a leading cause of heart disease and stroke, blood pressure management is crucial. Self-care management plays a vital role in maintaining the health of the elderly, but it is influenced by self-efficacy, which is the elderly's belief in their ability to effectively care for themselves and adhere to treatment. This study aimed to determine the relationship between self-efficacy and self-care management in elderly individuals with hypertension in the working area of the Rangkasbitung Community Health Center. The research employed a quantitative approach with a cross-sectional study design, and data analysis was performed using the Pearson Chi-Square test. Samples were selected using a purposive sampling method based on criteria predetermined by the researchers, followed by a quota sampling technique of 60 respondents who had a history of hypertension and were over 60 years old. The study results showed that 22 respondents (36.7%) had self-efficacy in the sufficient category, and 15 respondents (25%) were classified as lacking. Regarding self-care management, 40 respondents (66.7%) were in the poor category. The Pearson Chi-Square test yielded a p-value of 0.028, indicating a significant relationship between self-efficacy and self-care management in elderly individuals with hypertension.